A contribution to a better understanding of Zadar’s Renaissance fortifications - archaeological supervision of works on the restoration of the old Technical School (In situ, 2024)
Archaeological supervision of works on the renovation and reconstruction of the old Technical School building in Zadar at Šime Vitasovića Street was carried out in the period from October 2021 to June 2022. The remains of the connecting rampart Nani-Dolfin were documented during the archaeological supervision. From the middle of the 16th century until 1907, this rampart connected the Moro bastions, known as the bastion of St. Marcella and the Grimani bastion (presently harboring Queen Jelena Madijevka Park).
Keywords: Zadar; fortification system; Moro bastion; Grimani bastion